INTO THE DEPTHS OF THE HUMAN SOUL. AN OUTLINE OF PROTECTORATE PSYCHOLOGICAL PROSE - Sidakova Fialova, Alena (Bohemica Olomucensia, 2021)
The study deals with the problems of the Protectorate psychological prose, its form and changes in the period 1939-1945. It first characterizes general tendencies and backgrounds, then discusses individual authors. It describes the top works of the period, i.e. the novels of Vaclav Rezac and Jan Drda. It then describes a group of works that focus on exceptional characters, artists and doctors. Among the best known are Karel Schulz's The Stone and the Pain, and among the lesser known are the works of K. J. Benes, Cestmir Jerabek, Helena Dvorakova and others. Another section is devoted to specific works by younger authors such as Bohuslav Brezovsky, Vladimir Pazourek or Miroslav Hanus. They are united by the figure of a young man suffering for love, loneliness and the search for the meaning of life. A large part of the Protectorate's prose consisted of works dealing with interpersonal relationships, especially marital and lover's relationships (Vaclav Rezac, Jarmila Glazarova, Frantisek Kozik, Olga Barenyiova). Interpersonal relationships on the background of small-town life were the subject of several novels by Jaroslav Havlicek, and the work of Vladimir Neff also stands out from contemporary production.
Keywords: Protectorate; psychological prose; Jaroslav Havlicek; Vaclav Rezac